Audiovisual-Based Reproductive Health Education Program to Prevent Risky Sexual Behaviors - Fevriasanty, Fransiska Imavike; Merdikawati, Ayut; Yuliatun, Laily; Choiriyah, Muladefi (Caring: Jurnal Pengabdian Masyarakat, 2025)
Entering puberty, adolescents begin to feel sexual urges and an increase in curiosity about sexuality. This curiosity triggered adolescents to seek information and even try to engage in risky sexual behavior. Risky sexual behavior carried out by adolescents will have an impact. The purpose of this community service is to provide audiovisual-based reproductive health education to prevent risky sexual behavior in adolescents. The implementation of the education program in this series of community service was carried out on November 11-24, 2023, with 260 college students of the Faculty of Vocational Studies, Brawijaya University. Participants were divided into two groups, namely the intervention group (health education using audio-visual media) consist 130 college students and the control group (health education using leaflet) consist 130 college students. Evaluation was carried out through a questionnaire to measure parent-adolescent communication before and after the education program. The results showed that before and after being educated, the majority of adolescents had sufficient communication with their parents. There was an effect of reproductive health education on parent-adolescent communication in the intervention group as evidenced by the p-value of 0.041. Meanwhile, in the control group, there was no significant influence between reproductive health education and parent-adolescent communication and no significant difference was found between parent-adolescent communication in the intervention group and the control group. It suggests that while the intervention had a positive internal impact, it was not strong enough to produce a significant difference when compared to the control group.